Adhesive removable partial denture attachments made from zirconia ceramic: A finite element analysis and in vitro study - Orujov, Kamran; Winter, Werner; Karl, Matthias; Heckmann, Siegfried; Grobecker-Karl, Tanja (Journal of Prosthetic Dentistry, 2020)
Statement of problem: Whether adhesive zirconia ceramic removable partial denture attachments are feasible with current technology is unclear. Purpose: The purpose of this finite element analysis and in vitro study was to evaluate the effect of the lever arm, tooth preparation, and aging on the loading of the tooth-zirconia attachment interface. Material and methods: Three different finite element analysis (FEA) models allowing for the loading of an adhesive attachment either directly or through a removable partial denture were used. Two models represented a human tooth with 2 different types of attachments, while the third model also included a removable partial denture. For the evaluation of bond strength, a combination of shear and hydrostatic stress was used. In addition, composite resin teeth were fabricated, and zirconia bars were bonded to them with varying tooth preparations and lever arm lengths. In 1 group the influence of aging was analyzed. Fracture load was determined by using a universal testing machine. Statistical analysis was based on the Shapiro-Wilk normality test, ANOVA, and Games-Howell test (α=.05). Results: The maximum stress of 65 MPa occurring in the bonding area was reduced to 37 MPa by adding a retainer to the attachment. Loading of the denture resulted in a maximum stress of 9 MPa. Mean fracture loads ranged from 33.6 N to 209.1 N. Preparing a flat bonding surface showed a nonsignificant increase (P=.197), whereas aging led to a nonsignificant decrease in fracture load (P=.075). A lever arm extended by 2 mm significantly reduced fracture load (P=.002). The addition of an occlusal-distal (OD) cavity led to a nonsignificant increase (P=.186), which became significant when a mesial-occlusal-distal (MOD) preparation was applied (P=.001). Conclusions: Adhesive zirconia attachments should use a MOD cavity and have a cross section of at least 2.5×2.5 mm. The attachment should not extend more than 3 mm.
CRIS-Team Scopus Importer:2020-12-18